TABOO WORDS IN 33 MINUTES OF CHRISS ROCK YOUTUBE VIDEO: SOCIOLINGUISTICS STUDY - Sholeha, Siti Umi; Simatupang, Ervina CM (SAMPURASUN, 2024)
This research aims to classify types of taboo words and analyze the function of taboo words in Chris Rock's 33-minute YouTube channel; This research aims to classify types of taboo words and analyze their functions in Chris Rock's 33-minute YouTube performance. The study is based on the theories of Batistella (2005) and Raymond D. Liedlich (1973). Using a qualitative descriptive method, the data was sourced from the Laugh Planet YouTube Channel. The findings reveal three types of taboo words: obscenity, epithet, and profanity. Specifically, there were 3 instances of obscenity (1.7%), 1 epithet (5%), and 1 profanity (5%).  Additionally, four functions of taboo words were identified: creating attention, endearment, discredit, and providing catharsis. The analysis found 2 instances of creating attention (2.5%), 1 of endearment (5%), 1 of discredit (5%), and 1 of providing catharsis (5%). Among these, obscenity was the most frequently used type of taboo word, while creating attention emerged as the most common function. The study underscores the prevalence and diverse roles of taboo language in comedic performances, highlighting how such words are strategically employed to engage audiences, express affection, criticize, and release emotions. Chris Rock's skillful use of taboo language not only enhances his comedic impact but also reflects broader linguistic and social dynamics. This research contributes to a deeper understanding of the nuanced ways in which comedians use taboo words to connect with their audiences and convey complex messages, ultimately enriching the discourse on language and humor in contemporary media.